Icebergs versus Tariffs: A Quantitative Perspective on the Gains from Trade - Benjamin Jung; Gabriel Felbermayr; Mario Larch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We derive a simple equation for the welfare gains from trade when tariffs are liberalized or iceberg trade costs fall. Covering various one-sector trade models that may or may not feature extensive margins and imperfect competition, we generalize the analysis of Arkolakis, Costinot and Rodriguez-Clare (2012) to encompass revenue-generating import tariffs. Our formula permits easy quantification based on countries' observed degrees of openness, their tariff revenues, and gravity elasticities. We show analytically that an analysis based on iceberg costs necessarily underestimates the welfare gains from trade relative to autarky. Our quantitative exercise for 41 countries suggests that the bias can be numerically significant. For countries with relatively high status quo tariffs, our formula predicts 30-60% larger gains from trade than the icebergs only approach.
Keywords: F10; F11; F12; 330